Genetic background of resistance to gall mite in Ribes species - Mazeikiene, Ingrida; Bendokas, Vidmantas; Baniulis, Danas; Staniene, Grazina; Juskyte, Dovile Ana; Sasnauskas, Audrius; Stanys, Vidmantas; Siksnianas, Tadeusas (Agricultural and Food Science, 2017)
Resistance to gall mite is an important genetic trait of Ribes. P and Ce genes, responsible for gall mite resistance, were established in Ribes species and interspecific hybrids using molecular markers. Resistance in R. americanum is determined by P gene and in R. sanguineum by Ce gene. Both molecular markers were absent in R. dikuscha genome. Molecular markers related to P and Ce genes were identified in the genome of R. aureum. Resistance to gall mite in the field conditions in R. nigrum x R. americanum, R. nigrum x R. aureum and R. nigrum x R. sanguineum F3 hybrids fitted an expected Mendelian segregation ratio of 1:1, 3:1 and 1:1, respectively. 75.0% of hybrids with a pyramidal resistance to gall mite carrying markers related to Ce and P genes were obtained in the cross combination R. nigrum x R. aureum and will be included in the future breeding programs.